2017
DOI: 10.1111/acfi.12296
|View full text |Cite
|
Sign up to set email alerts
|

Are paper winners gamblers? Evidence from Australian retail investors

Abstract: This study examines stock market gambling using a comprehensive set of investor characteristics and past portfolio performance measures. We find that retail investors overinvest in ‘lottery stocks’, stocks with gambling‐like properties. Significant portfolio underperformance is the result of gambling through lottery stocks. Investors are more likely to gamble following recent portfolio paper gains, regardless of realised performance, providing new evidence that paper gains trigger a house money effect. Investo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…For example, each 1% increase in the previous month's portfolio return leads to an increase of about 0.21% in their lottery stock holding, and each 1% increase in the current month's portfolio return leads to an increase of about 0.06% in their lottery stock holding. This is consistent with the house money effect reported in Frino et al (2019). Previous and concurrent market performance appear to affect lottery stock investment in the opposite way; when the market is performing better, lottery stock holdings become lower.…”
Section: Research Findingssupporting
confidence: 93%
See 4 more Smart Citations
“…For example, each 1% increase in the previous month's portfolio return leads to an increase of about 0.21% in their lottery stock holding, and each 1% increase in the current month's portfolio return leads to an increase of about 0.06% in their lottery stock holding. This is consistent with the house money effect reported in Frino et al (2019). Previous and concurrent market performance appear to affect lottery stock investment in the opposite way; when the market is performing better, lottery stock holdings become lower.…”
Section: Research Findingssupporting
confidence: 93%
“…Existing studies establish that investors with greater lottery stock holding weights underperform compared to other investors. It has also been reported that, while it is possible that some investors hold more lottery stocks due to the larger size of their portfolio, performance comparison based on portfolio‐size‐adjusted lottery stock weights leads to the same conclusion: investment portfolios with greater lottery stock weights achieve lower returns (Frino et al, 2019; Kumar, 2009). In this study, in addition to comparing the performances of different lottery holding groups and different age cohorts, we raise the following question: as the participation of investor birth cohorts in the stock market is time varying, and certain birth cohorts are more prone to hold lottery stocks, will the level of the presence of these cohorts in the market affect the returns of lottery stocks?…”
Section: Sample Data and Research Methodsmentioning
confidence: 94%
See 3 more Smart Citations